Peran Youtube Sebagai Media Dakwah: (Studi Kasus Akun Youtube Adi Hidayat Official) - Satria Dirgantara Pasaribu; Khairil Anwar (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2025)
This research is entitled "The Role of Youtube as a Media of Da'wah (Case Study of Adi Hidayat Official Youtube Account)". The purpose of this research is to find out how the role of YouTube as a propaganda medium. This study uses the uses and gratification theory with a qualitative descriptive method, the material in this study was obtained from an analysis of the development of Adi Hidayat Offiicial's YouTube account. The place of research was conducted at the researcher's house, which is located at Jalan Ilyas No. 27A Rt. 005/03, Ex. North Sukabumi, Kec. Kebon Jeruk, West Jakarta. The time of the research was carried out from June to July 2021. The subject of this research is the Adi Hidayat Official YouTube account. The object of this research is a video lecture that is distributed through the Adi Hidayat Official YouTube account. The data collection method in this study was conducted by non-participant observation from two data sources, namely, primary data obtained from the number of viewers and secondary data obtained from the movement of audience responses. The results of this study are the role of YouTube for Ustadz Adi Hidayat in spreading da'wah through YouTube is to make da'wah more practical, make the number of subscribers / followers increase, get a wider (global) audience, and make da'wah follow the times.